(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This study investigates the therapeutic effects of omega-3 fatty acids on anemic rats. Forty male rats were fed a baseline diet prepared by the American Institute of Nutrition (AIN). Anemia was induced in two groups of rats using a bleed-out procedure, with hemoglobin levels at 11 g/dL or lower and hematocrit levels at 33% or lower indicating anemia. Following acclimatization, the rats were randomly assigned into four groups of ten rats each: control group (G1), omega-3 supplemented group (G2) receiving 300 mg/kg/day for two weeks, untreated anemic group (G3), and omega-3 treated anemic group (G4) receiving 300 mg/kg/day for two weeks. Blood samples were collected at the start and 28 days into the experiment using the orbital venous plexus method. Hematological parameters were analyzed using a hematology autoanalyzer, and statistical analysis was performed using SPSS version 23. Results showed that G1, G2, and G4 had similar erythrogram and leukogram parameters with no significant differences (indicated by the letter A). In contrast, G3 exhibited significantly lower values (indicated by B) in mean corpuscular hemoglobin concentration (MCHC), mean corpuscular hemoglobin (MCH), mean corpuscular volume (MCV), hemoglobin (Hb), packed cell volume (PCV), red blood cell count (RBC), mid-sized cells (Mid), granulocytes (Gran), lymphocytes (L), and total white blood cell count (WBC). These findings suggest that the anemia had a detrimental impact on both erythrogram and leukogram parameters, while omega-3 supplementation improved these parameters, indicating its potential as a therapeutic agent for anemia.